International Differences in Income Velocity - Melitz, Jacques; Correa, Hector (The Review of Economics and Statistics, 1970)
INCOME velocity studies have centered thus far on a few countries, mostly the United States. The present effort deals with international differences in income velocity. While there have been a number of far-reaching international monetary studies of hyperinflation,' to our knowledge only limited work has been done on international differences in income velocity.2 Our approach is to try to explain international differences in income velocity on the basis of a simple demand for money equation, and thus to view the money supply as determined exogenously. This accords with the usual econometric treatment of income velocities.3 The approach may seem rather naive at present, in the light of institutional differences in world monetary environments and statistical discrepancies in national accounts. However, our aim is not to produce structural estimates of income velocity, but to isolate some major influences on income velocity. Accordingly, we have included as many countries as possible in the study, spanning 1958 through 1965 51 at some points and 45 for the rest. We find three statistically significant variables, all operating with the theoretically appropriate sign: the rate of interest, the currency-money ratio, and the degree of monetization. The favorable outcome regarding the interest rate, despite other variables in the equations reflecting inter-country differences in structural environment, is particularly noteworthy. Another important result is that the level of economic development is not an independent influence on income velocity.